Pelatihan Edukasi Kesehatan Reproduksi (Seks Pranikah Dan Bahaya Narkoba Pada Remaja - Ratna Ratna; Nur Khalid; Darwis Darwis; Muzakkir Muzakkir (STKIP Andi Matappa, 2023)
This community service aims to provide clear information and health education for teenagers about the dangers of promiscuity and abuse. drugs among teenagers. This activity uses the lecture method accompanied by mentoring for teenagers who during the activity. Mentoring is done with a Learning is fun approach. The target of youth activities is the age range of 13-16 years. The results of the activity show that adolescents have good knowledge and attitudes about the dangers of promiscuity and drug abuse with indicators capable of mentioning the impact of the dangers of promiscuity and drug abuse among adolescents and showing the behavior of refusing drug abuse and promiscuity among adolescents. This success can also be seen from the enthusiasm of adolescents. in participating in each activity session. It is hoped that the activities will continue to increase the knowledge, attitudes and social awareness of adolescents.